(untitled) - Williamson, Richard E. (New York, 1996)
The book integrates many of the classic ideas of differential equations and the more modern study of dynamical systems into an introductory course in differential equations. It also provides a variety of relevant applications of differential equations within framework of a traditional course
Keywords: Differential dynamical systems,Differential equations